Titania Nanobelts as a Scattering Layer with Cu2ZnSnS4 as a Counter Electrode for DSSC with Improved Efficiency. (2018) - Nemala, Siva Sankar; Mokurala, Krishnaiah; Bhargava, Parag; Mallick, Sudhanshu
Abstract: Various nanostructures of Titania (TiO2 ) play a significant role in the performance of dye sensitized solar cells (DSSCs) and affect the overall light harvesting efficiency of the cells. In this article we present the one dimensional nanostructure of TiO2 (nanobelts) can increase the light scattering effect, light harvesting effect and electron transport in the DSSC to improve its performance. Pure anatase TiO2 nanobelts were synthesized by a hydrothermal method using commercial material (P25) and characterized by XRD and SEM. Cu2 ZnSnS4 (CZTS) nanoparticles have been prepared by thermal decomposition method used as counter electrode material instead of platinum. DSSC have been fabricated by using a new type of double layered photoanode, which was prepared and optimized by using TiO2 nanoparticles as the main layer and TiO2 nanobelts as the over-layer (scattering layer). The photoelectric conversion efficiency (PCE) of the prepared cells was measured by solar simulator under 1 sun illumination (100 mW/cm 2, AM 1.5). The DSSCs with CZTS nanoparticles based counter electrodes without scattering layer relatively low PCE of 5.76 %. However, the PCE was clearly improved with scattering layer and a maximum PCE of 7.85% was achieved.